Clinical Utility of Plasma Fructosamine Concentration as a Hypoglycemic Biomarker during Early Lactation in Dairy Cattle. (9th February 2018) - Megahed, A.A.; Hiew, M.W.H.; Constable, P.D.
Abstract : Background: Plasma fructosamine concentration ([FRA]) is a widely used long term hyperglycemic biomarker in humans and dogs, but its clinical usefulness as a hypoglycemic biomarker in dairy cattle is uncertain. Objectives: To evaluate the relationship between plasma [FRA] and glucose concentration ([gluc]) as well as indices of energy balance during early lactation in dairy cattle, and to characterize the influence of plasma total protein concentration ([TP]) and albumin concentration ([albumin]) on [FRA]. Animals: Convenience sample comprising 103 periparturient Holstein–Friesian cattle. Methods: Plasma [gluc], [TP], [albumin], and other clinicopathologic indices of energy status were determined periodically from Day 4 postpartum. Body condition score (BCS) was assessed, and backfat thickness (BFT) and longissimus dorsi muscle thickness (LDT) were measured ultrasonographically. Plasma [FRA] was measured at approximately 28 days postpartum. Associations between plasma [FRA] and study variables were evaluated using Spearman's rho and stepwise forward linear regression. Statistical significance was declared at P  < 0.05. Results: A positive association was detected between plasma [FRA] and mean plasma [gluc] from Days 4–28 postpartum ( r s  = +0.36, P  < 0.001), and between plasma [FRA] and LDT ( r s  = +0.28, P  = 0.007), BCS ( r s  = +0.23, P  = 0.029), and BFT ( r s  = +0.21, P  = 0.043). Multivariable regression identified a positive association between plasma [FRA] and mean plasma [gluc] and [albumin] from Days 4–28 postpartum. Correcting plasma [FRA] for [albumin] improved the association ( r s  = +0.46, P  < 0.001) between plasma [FRA] and mean plasma [gluc]. Conclusions and Clinical Importance: Plasma [FRA] does not provide a clinically useful method for quantifying the magnitude of hypoglycemia or negative energy balance in dairy cows during early lactation.